APLIKASI VIDEO KONFERENSI BERBASIS WEB DENGAN FITUR FACE RECOGNITION UNTUK VERIFIKASI IDENTITAS PESERTA - Fathurrahman; Muniar, Andi Yulia; Abdul Kadir Parewe, Andi Maulidinnawati; Angriawan, Randy; Yusa Wardhani, Dyah Utari Yusa Wardhani (JURNAL TELISKA, 2024)
This research aims to develop a website-based application that makes it possible to automatically verify the identity of participants in video conferences using facial recognition technology. This application was created to make the participant identification process easier compared to conventional methods which often take longer. The process of creating this application includes several stages, namely literature study to understand relevant technology, user interface design, application design, implementation of the face recognition feature, and application testing using black box and questionnaire methods. Based on the results of this research, the results obtained show that this application is able to verify participant identity automatically through its facial recognition feature and shortens the time for verifying participants. This was obtained through tests that have been carried out with various scenarios to ensure its performance. Testing was carried out with several participants and different conditions, such as the use of face masks and filters, low video quality, and inappropriate participant faces.